Construction of Theory and Concept of Digital-Based PAI Learning Assessment - Abdul Muqtadir S; Asmiatin Asmiatin; Khoiri Khoiri; M. Fattahuddin; Abdul Halik (Journal of Pedagogi, 2025)
The development of information and communication technology (ICT) has brought significant changes to various aspects of life, including the field of education. One area that is directly affected is the learning assessment system, particularly in the subject of Islamic Religious Education (PAI). Digital-based PAI assessment has emerged as an innovative solution to address the demands of the times, which require efficiency, transparency, and accountability in evaluating learning outcomes. This article examines the theoretical and conceptual construction of digital-based PAI assessment, including its definition, implementation examples, and the challenges encountered. This study employs a qualitative approach through a literature review, with data collected from the latest relevant scientific literature, both national and international. The findings indicate that digitalization in PAI assessment can enhance the effectiveness of learning data collection, provide real-time feedback to students, and support a more adaptive and personalized learning approach. Commonly used platforms include Google Forms, Quizizz, Moodle, and other Learning Management Systems (LMS). Although it offers many advantages, several obstacles remain, such as limited technological infrastructure, low digital literacy among teachers and students, and resistance to shifting from traditional evaluation methods. Therefore, educational policy support is needed to ensure continuous teacher training, adequate technological facilities, and a curriculum that adapts to technological developments.